Crystal Structure and Spectroscopic Analysis of 3-Diethoxyphosphoryl-28-[1-(1-deoxy-β-D-glucopyranosyl)-1H-1,2,3-triazol-4-yl]carbonylbetulin - Monika Kadela-Tomanek; Ewa Bębenek; Arkadiusz Sokal; Maria Książek; Elwira Chrobak (Crystals, 2023)
The molecular structure of 3-diethoxyphosphoryl-28-[1-(1-deoxy-β-D-glucopyranosyl)-1H-1,2,3-triazol-4-yl]carbonylbetulin was investigated through various experimental and theoretical methods. X-ray diffraction, Hirshfeld surface, experimental and calculated FT-IR spectra analysis, molecular electrostatic potential (MEP) and molecular orbital (HOMO and LUMO) were used for the analyses. It was found that the introduction of a triazole substituent affects the arrangement of molecules in the crystal structure and the formation of hydrogen bonds. The Hirshfeld surface analysis shows that the red regions are concentrated near groups, which create hydrogen bonds, which means that the hydrogen bonds are strong. The analysis of HOMO and LUMO orbitals and the chemical reactivity descriptors shows that the compound is kinetically and chemically stable. A molecular electrostatic potential map was used to analyze the electrophilic and nucleophilic area in the molecule.